2015
DOI: 10.1038/ejhg.2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic CWF19L1 variants as a novel cause of autosomal recessive cerebellar ataxia and atrophy

Abstract: Autosomal recessive cerebellar ataxia (ARCA) is a group of neurological disorders characterized by degeneration or abnormal development of the cerebellum and spinal cord. ARCA is clinically and genetically highly heterogeneous, with over 20 genes involved. Exome sequencing of a girl with ARCA from non-consanguineous Dutch parents revealed two pathogenic variants c.37G4C; p.D13H and c.946A4T; p.K316* in CWF19L1, a gene with an unknown function, recently reported to cause ARCA in a Turkish family. Sanger sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 10 publications
5
32
1
Order By: Relevance
“…The novel mutation c.467delC leads to a frameshift starting at amino acid 156 (shown by a red arrow) which results in a putative premature stop codon at amino acid 189 (marked by an red asterisk). The location of the mutations reported by Burns et al [] and Nguyen et al [] is indicated by black arrows. The c‐terminal parts of C19L1 against which the antibodies are raised are indicated by a blue or grey box (antibodies HPA036890 and PA5‐31646, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel mutation c.467delC leads to a frameshift starting at amino acid 156 (shown by a red arrow) which results in a putative premature stop codon at amino acid 189 (marked by an red asterisk). The location of the mutations reported by Burns et al [] and Nguyen et al [] is indicated by black arrows. The c‐terminal parts of C19L1 against which the antibodies are raised are indicated by a blue or grey box (antibodies HPA036890 and PA5‐31646, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The advent of next‐generation sequencing technologies has facilitated the discovery of novel genes. Very recently, biallelic mutations in CWF19L1 (complexed with cdc5 protein 19‐like 1) were reported in two families with early onset cerebellar ataxia and cognitive impairment [Burns et al, ; Nguyen et al, ]. CWF19L1 knockdown in a zebrafish model leads to abnormal cerebellar morphology and function [Burns et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Standard filter steps were location (exonic and canonical splice, the latter defined as ≤2 nucleotides intronic), sequencing depth/reads (≥8), and zygosity (homozygous variants removed). Variably applied filter steps were amino acid alteration (synonymous variants removed), annotation in databases (HGMD and/or ClinVar), allele frequency (dbSNP <5% versus <1%), mutation type (frameshift, nonsense, splice site, missense), presence of identical variants in both partners of the couple, presence of variants in the same genes in both partners of the couple, and presence of variants in genes included in gene panels.…”
Section: Discussionmentioning
confidence: 99%
“…For family MR106 with a CWF19L1 homozygous variant and family MR90 with a TUSC3 homozygous variant, seizures were observed in some family members. Seizure has not been previously reported as a feature of CWF19L1- and TUSC3- related ARID (Burns et al 2014; Nguyen et al 2016; Evers et al 2016; Garshasbi et al 2008, 2011; Khan et al 2011; Loddo et al 2013; Al-Amri et al 2016). Interestingly TUSC3 belongs to the same gene family as ALG3 , which is associated with congenital disorders of N-linked glycosylation that commonly include seizures as a feature (Table 1; Garshasbi et al.…”
Section: Discussionmentioning
confidence: 85%
“…Unless indicated, these variants were absent in 194 unrelated Pakistani exomes with non-cognitive Mendelian phenotypes and in ~ 1000 unrelated individuals in the GME Variome Project. References per known gene: ALG3 (Riess et al 2013); ASPM (Kousar et al 2010); BCKDK (Novarino et al 2012); CRADD (Di Donato et al 2016; Harel et al 2017); CWF19L1 (Burns et al 2014; Nguyen et al 2016; Evers et al 2016); CYB5R3 (Ewenczyk et al 2008); GAN (Kuhlenbäumer et al 2002; Tazir et al 2009); LRP2 (Vasli et al 2016); MBOAT7 (Johansen et al 2016); MLYCD (Salomons et al 2007); PNKP (Shen et al 2010); SPTBN2 (Lise et al 2012); TUSC3 (Garshasbi et al 2008, 2011; Khan et al 2011; Loddo et al 2013; Al-Amri et al 2016); WDR62 (Wang et al 2017). …”
Section: Figmentioning
confidence: 99%